The effect of entrepreneurship education on entrepreneurial intention: The mediating role of personal innovativeness and self-efficacy - Vu Tuan, Duong; Nguyen Hoang, Nam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The study applies the Social Identity Theory to propose a model of the factors influencing entrepreneurial intentions. Based on data collected from 410 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), the results reveal several key findings. Firstly, both innovative spirit and self-efficacy beliefs positively impact students’ entrepreneurial intentions. Secondly, entrepreneurship education emerges as a significant predictor of both innovative spirit and self-efficacy beliefs. Notably, innovative spirit and self-efficacy beliefs jointly mediate the relationship between entrepreneurship education and students’ entrepreneurial intentions. These findings have important implications for university administrators and policymakers seeking to foster a conducive environment for student entrepreneurial behavior.
Keywords: Entrepreneurship; Entrepreneurship education; Personal innovativeness; Self-efficacy; Entrepreneurial intention